Chemical composition and biological activities of the essential oil from the leaves of Vaccinium myrtillus L. (Bangladesh Journal of Botany, 2020)
The chemical composition, antimicrobial and antioxidant properties of the essential oil (EO), obtained from the leaves of Vaccinium myrtillus naturally grown in the northernmost of Turkey were determined by GC and GC-MS and chemical differences were discussed with the help of chemotaxonomy. The leaves of the plant samples were hydro-distilled to produce oil in the yields of 1%. Nineteen components were identified representing 96.4% of the oil. The main compounds in the EO of V. myrtillus were; 1,8-cineole (38.6%), α- pinene (21%), linalool (19.5%), α-terpineol (5.8%). The EO extract was screened for their antimicrobial activities against the 9 bacteria and 3 yeast species by using disc-diffusion and MIC procedure. The EO extract displayed more effective against all the tested bacteria (especially, S. aureus ATCC 6538 and MRSA) and yeast (only C. krusei). The MIC values of sample against tested microorganisms were found to be in the range of 320 to ≥1280 μg/ml. The most effective MIC values were observed against the S. aureus and MRSA (320 μg/ml). In vitro the antioxidant activity based on the 1,1-diphenly-2-picrylhydrazyl (DPPH) free radical was evaluated for the EO extract, and it was found that the extract had good antioxidant activity in the range of the IC50 = 583.4 ±11 μg ml. Antibacterial and antioxidant activities of the EO from the leaves of V. myrtillus has been reported for the first time.